Evolution of the mexican economy against COVID-19 outbreaks: implications and perspectives - Mendoza Gutiérrez, Abdiel (2022)
More than a year later, the resurgence of infections does not bode well for a son return to normalcy. It was different implication in diverse areas. Then, the objective of this document is to show the economic impact of the outbreaks of COVID-19 and its implications and perspectives for the Mexican economy. For data analysis, a forecast based on time series was made. The GDP forecast indicates that it will not present drastic changes during the year 2022. About remittances, they are expected to decline in the coming months but then resume their upward trend. For the unemployment rate, is expected to decrease in the coming months, to return to the same level later and to decrease again at the end of 2022. For the national index of prices and quotations, the forecast shows that for December 2022. It is expected that the Monthly Consumption Index will continue to grow, as it has been doing over time, even after the abrupt fall that 2020 suffered. Finally, the price and quotation index show a tendency to remain stable over the next few months and for the exchange rate series, it is expected to continue growing gradually over the next few months. These results show the importance of mathematical models to understand the economic outlook and are a necessary tool for decision-making.